KINERJA PERBEDAAN SALINITAS TERHADAP RESPON PERTUMBUHAN DAN GAMBARAN DARAH BENIH IKAN TAMBAKAN (Helostoma temminckii) - Lies Setijaningsih; Imam Taufik; Deni Radona; Mulyasari Mulyasari (BERITA BIOLOGI, 2020)
Water salinity is a crucial factor in Kissing Gourami (Helostoma temminckii) culture. Therefore, information regarding suitable and optimum medium for the ecophysiological requirement of fish is needed. Salinity is one physiological factor that affects both the survival and growth rate of fish as it is related to the osmoregulation process. The purpose of this study was to analyze the effect of different water salinity on, growth, survival rate, osmotic activity and blood picture of Kissing Gourami seed nursery. Fish was cultured in various salinity levels: 0 ppt (A), 1 ppt (B), 3 ppt (C), and 5 ppt (D). Salinity level significantly affected the survival rate, absolute weight growth, absolute length growth, specific growth rate, and blood picture of Kissing Gourami seed nursery. It was found that the Kissing Gourami seeds had the optimum growth on the salinity of 3 ppt, that was further shown by 82,00% of survival rate, 2,42% ±2,81 g/day of specific growth rate obtained. The results showed a positive correlation of the biological value of fish with the content of osmotic gradient, blood glucose, hematocrit, hemoglobin, erythrocytes amount, and water quality parameters (dissolved oxygen, temperature, pH, and ammonia).